Effect of HF concentration on corrosion resistance of biomedical implants - Assadian, Mahtab (2012)
This work compared the variation of weight of Mg 1%Ca as cast in different concentrations of hydrofluoric acid (HF) such as 45% - 40% - 35% - 25% - 20 % - 13% - 7 % for 24 h at room temperature to be utilized in biomaterial application like hip, knee implants that have effect on corrosion resistance. By immersion Mg 1%Ca alloys in HF, the layer of MgF2 was constituted on the surface of alloy and this layer improves the corrosion and causes weight gain. The results show that in order to get a better corrosion resistance, surface treatment should be done in 40% of HF, because the weight gain is more than other HF concentrations.